2020
DOI: 10.1007/s00442-020-04746-1
|View full text |Cite
|
Sign up to set email alerts
|

Functional diversity of habitat formers declines scale-dependently across an environmental stress gradient

Abstract: Marine habitat formers such as seaweeds and corals are lynchpins of coastal ecosystems, but their functional diversity and how it varies with scale and context remains poorly studied. Here, we investigate the functional diversity of seaweed assemblages across the rocky intertidal stress gradient at large (zones) and small (quadrat) scales. We quantified complementary metrics of emergent group richness, functional richness (functional space occupied) and functional dispersion (trait complementarity of dominant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 104 publications
0
10
0
Order By: Relevance
“…For example, an increase in disturbance can create heterogeneous habitats with a high variation in environmental conditions in spatially adjacent locations. This increase in heterogeneity may lead to opportunities for species with different requirements to coexist, thus reflecting significant trait divergence at site (Gross et al 2013, Cappelatti et al 2020) and landscape scales (Mendes et al 2016). Once species overcome the dispersal barrier and fit the environmental conditions of a given site, species interactions then determine which species can integrate a community (as per community assembly theory, see HilleRisLambers et al 2012 for an extensive review on this topic).…”
Section: Introductionmentioning
confidence: 99%
“…For example, an increase in disturbance can create heterogeneous habitats with a high variation in environmental conditions in spatially adjacent locations. This increase in heterogeneity may lead to opportunities for species with different requirements to coexist, thus reflecting significant trait divergence at site (Gross et al 2013, Cappelatti et al 2020) and landscape scales (Mendes et al 2016). Once species overcome the dispersal barrier and fit the environmental conditions of a given site, species interactions then determine which species can integrate a community (as per community assembly theory, see HilleRisLambers et al 2012 for an extensive review on this topic).…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that the effects of the algal community on crustacean diversity cannot be entirely attributed to increased algal cover alone. Given the importance of the algal community on crustacean diversity in this study, future examinations of how algal communities respond to environmental parameters (Cappelatti et al 2020) and how crustacean diversity is related to other components of algal diversity, such as functional diversity (Mauffrey et al 2020), could further illuminate the mechanisms underlying the relationship between crustacean and algal diversity.…”
Section: Discussionmentioning
confidence: 99%
“…In marine systems, much of the research on functional and/or phylogenetic diversity has focused on microbial communities (Barberán and Casamayor 2010;Bryant et al 2012;Galand et al 2015), corals (Wong et al 2018), fish communities (D'agata et al 2014;Plass-Johnson et al 2016;Tuya et al 2018), and algae (Mauffrey et al 2020;Cappelatti et al 2020). Many of these studies demonstrated variation in functional and phylogenetic diversity along environmental gradients-such as depth (Bremner et al 2003;Pacheco et al 2010;Bryant et al 2012;Tuya et al 2018) or shore height (Cappelatti et al 2020)similar to patterns often seen with taxonomic diversity. Trait diversity may also be an important factor structuring community coexistence in some habitats; for example, Best and Stachowicz (2014) found that crustacean communities in eelgrass beds (primarily amphipods and isopods) were composed of distantly related species that were divergent in both body size and phenological traits.…”
Section: Communicated By E Macphersonmentioning
confidence: 99%
“…The differences of FD (i.e., FRich, FEve, FR) across sites and seasons could be determined by several factors: (i) abundance, diversity and taxa, and (ii) specific environmental conditions and benthic habitat characteristics (e.g. sediment organic matter, grain size, sorting), as described in previous studies (e.g., Hewitt et al, 2008;Shojaei et al, 2015;Henseler et al, 2019;Cappelatti et al, 2020). FRic and FR were greater across all the sites in summer compared to winter, suggesting that the expression of traits was greater in summer.…”
Section: Patterns Of Taxonomic and Functional Metricsmentioning
confidence: 96%